Start-up rates and innovation: A cross-country examination - Anokhin, Sergey; Wincent, Joakim (Journal of International Business Studies, 2012)
Despite the widespread assumptions of the positive relationship between start-up rates and innovation, the empirical support for this conjecture in the cross-country context is largely lacking. We draw upon recent advances in the entrepreneurship literature to propose that the relationship between start-up rates and innovation is not uniformly positive, as expected by the early scholars of entrepreneurship, but instead depends on the country's stage of development. The relationship is positive in the developed countries, but negative in countries in early development stages. On balance, there is a weak negative association between start-up rates and innovation. We test our hypotheses on a multi-source dataset that covers 35 countries over the period from 1996 to 2002. The relationships are robust to the choice of three moderators and two dependent variables, as well as a number of post-hoc tests. Our findings indicate that broad-strokes policy efforts that aim at promotion of entrepreneurship as a means to boost country innovativeness may be misguided, and instead suggest a contingency approach.